E-PKBM Training for Tutors for Equal Learning - Sukestiyarno, Yl; Rahayu, RR. Sri Ratna; Kriswanto, Hendra Dedi (Jurnal Abdimas, 2023)
Education is considered very important in increasing human cognitive, affective and psychomotor potential. However, there are still many people who do not have access to education, especially in Pemalang Regency. This happens because the community's economic condition is still weak, educational service facilities are minimal and geographical conditions are very far apart even though the Government has implemented 12 years of compulsory education. There is data on access to education through equality education for 4,277 students with only 54 tutors, so it is still very lacking. This has an impact on the low quality of learning outcomes. The aim of community service is to provide training or assistance to tutors in Pemalang Regency in implementing E-PKBM as distance learning for equality education. The methods used are lectures, discussions and training or mentoring. The data obtained was processed descriptively. The results of this training activity show that the tutor has gained an understanding of the role of E-PKBM in the learning process and the tutor has understood how to use existing E-PKBM features to make learning easier. The conclusion from this activity is that tutors can create distance learning by utilizing E-PKBM.